1H and 19F NMR in drug stress testing: the case of voriconazole. Issue 54 (5th July 2017) - Barbosa, T. M.; Morris, G. A.; Nilsson, M.; Rittner, R.; Tormena, C. F.
Abstract : Stress tests form an important part of drug development, and of subsequent accreditation. Abstract : Stress tests form an important part of drug development, and of subsequent accreditation. Commonly the change in chemical composition over time is determined using chromatographic methods that separate the mixture components, but when structural characterization of the degradation products is required, other methods are needed. Arguably the most powerful method for determining chemical structure information is NMR spectroscopy. Here we show that NMR alone, using a combination of simple 19 F, 1 H, and DOSY experiments, can characterise both structure and kinetics of an intact reaction mixture, without the need for any physical separation.